2016
DOI: 10.1007/s12664-016-0646-z
|View full text |Cite
|
Sign up to set email alerts
|

Lower relapse rates with good post-transplant outcome in alcoholic liver disease: Experience from a living donor liver transplant center

Abstract: Good results can be obtained following LDLT for ALD, with significantly lower relapse rates in our setup as compared to the West.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The current series shows higher morbidity and mortality in patients with significant drinking (recidivism) after LT for ALD than in those who do not relapse. LT for ALD is associated with good survival rates; 11 however, the long-term survival is poor in patients with recidivism, likely secondary to graft loss or de novo malignancies. 1,2,[5][6][7][8] While patients with occasional alcohol intake have similar outcomes, recidivism is shown to be associated with poor survival after LT. A meta-analysis of 90 studies showed 22% alcohol relapse (95% confidence interval [CI]: 19-25%) and 14% heavy alcohol relapse (95% CI: 12-16%) at a mean follow-up of 48.4 AE 24.7 months after LT. 12 Several studies have shown poor outcomes in patients with recidivism as compared with those with no or occasional alcohol intake after undergoing LT for ALD.…”
Section: Discussionmentioning
confidence: 99%
“…The current series shows higher morbidity and mortality in patients with significant drinking (recidivism) after LT for ALD than in those who do not relapse. LT for ALD is associated with good survival rates; 11 however, the long-term survival is poor in patients with recidivism, likely secondary to graft loss or de novo malignancies. 1,2,[5][6][7][8] While patients with occasional alcohol intake have similar outcomes, recidivism is shown to be associated with poor survival after LT. A meta-analysis of 90 studies showed 22% alcohol relapse (95% confidence interval [CI]: 19-25%) and 14% heavy alcohol relapse (95% CI: 12-16%) at a mean follow-up of 48.4 AE 24.7 months after LT. 12 Several studies have shown poor outcomes in patients with recidivism as compared with those with no or occasional alcohol intake after undergoing LT for ALD.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies are retrospective in nature and have used various definitions of relapse or recidivism, which makes a comparison difficult. Usually relapse is defined as any amount of alcohol intake after LT. 1,32 As discussed earlier, significant drinking (and not occasional alcohol intake) is important for prognosis. There are several definitions of significant drinking used in various studies.…”
Section: Predictors Of Relapsementioning
confidence: 97%
“…All heavy drinkers presented with features of graft dysfunction. 1 Thus patients with occasional alcohol intake appear to have similar outcomes; however, those with significant alcohol intake are associated with poor survival after LT.…”
mentioning
confidence: 99%
See 2 more Smart Citations